Yellow rust threat in wheat under extreme cold in North Western India: GIS linked risk map for disease monitoring - Sinha, P; Kamble, Kalpana; Singh, Vivek; Ritesh, Ritesh; Sharma, Taru; Singh, U D; Gogoi, Robin; Bal, R S; Pathak, Himanshu; Sehgal, V K (Indian Farming, 2015)
Climate change is causing extreme events like cold waves, drought or excessive rainfalls and floods, cyclones. Managing risks due to such extreme events and associated disasters should be the priority in advance to climate change adaptation. Under emerging scenario for yellow rust, weather based indices linked to GIS would be useful to provide not only sound rust management programme but also helps in searching sources of resistance or tolerance against the disease for wheat improvement programmes. Development of risk map is a demonstration how the system can be used to show regional monitoring where wheat is a major crop.